Echocardiographic Parameters to Predict Atrial Fibrillation in Clinical Routine—The EAHsy-AF Risk Score - Sieweke, Jan-Thorben; Hagemus, Jan; Biber, Saskia; Berliner, Dominik; Grosse, Gerrit M.; Schallhorn, Sven; Pfeffer, Tobias Jonathan; Derda, Anselm A.; Neuser, Jonas; Bauersachs, Johann; Bavendiek, Udo (Frontiers in Cardiovascular Medicine, 2022)
Background: Echocardiographic parameters representing impaired left atrial (LA) function and remodeling are of high value to predict atrial fibrillation (AF). This study aimed to develop a prediction model for AF easily to apply in clinical routine containing echocardiographic parameters associated with LA remodeling and - function. Methods and Results: This monocentric, semi-blinded, controlled analysis included 235 patients to derive a prediction model. This prediction model was tested in a validation cohort encompassing 290 cardiovascular inpatients. The derivation and validation cohort included 54 (23%) and 66 (23%) patients with AF, respectively. Transthoracic echocardiography, comprising parameters indicating left atrial remodeling (septal/lateral total atrial conduction time (s/l PA-TDI)) and left atrial volume indexed to a` (LAVI/a`) was performed in each patient. Based on multivariable regressions analysis, four variables were enclosed into the EAHsy (Echocardiography, Age, Hypertension)-AF risk score for AF prediction: Hypertension, Age, LAVI/a` and septal PA-TDI. In the validation cohort discrimination was strong (C-statistic 0.987, 95%CI 0.974-0.991) with an adequately performed calibration. The EAHsy-AF risk score was associated with a more precise prediction of AF in comparison to commonly used AF-scores (CHADS2-, ATLAS-, ARIC-, CHARGE-AF score). Conclusion: The EAHsy-AF-Score containing age, hypertension and echocardiographic parameters of atrial dysfunction and remodeling precisely predicts the incidence of AF in a general population of patients with cardiovascular disease. The EAHsy-AF risk score may enable more selective rhythm monitoring in specific patients at high risk for AF